Russian oil output - Midkhatovich, S (Oxford Institute for Energy Studies, 2009)
In September–October 2009, Russia made headlines when its oil exports in the second quarter of 2009 surpassed that of the world’s largest oil supplier, Saudi Arabia. In April–June 2009, Russia exported 7.4 million barrels of oil per day compared to Saudi Arabia’s oil exports of 7 million barrels. In addition, in the middle of 2009 Russian oil output reached a ten-year record of 9.91 million barrels per day. At first glance, it may appear that the global financial meltdown has not made a severe impact on the Russian oil industry. However, the Russian reality is rather different if not complex. First, it can be argued that the recent increase in Russian oil exports was primarily driven by external market conditions rather than domestic policies. In fact, Russian government policies of the past eight years promoted the stagnation rather than the development of the oil sector. Secondly, although according to official data for the second quarter of 2009 Russia surpassed the other top oil-producing nation, Saudi Arabia, in terms of oil exports, it actually was placed worst amongst all G20 countries in terms of economic performance during the crisis of 2009. Quite notably, in April–June 2009 in comparison to Saudi Arabia’s GDP decline of 0.9 percent, Russia’s GDP fell by as much as 10.9 percent. Poor economic performance in Russia is linked not only to the sudden fall of oil prices within the second half of 2008, but also to the manner in which the government’s fiscal policies and taxation of the domestic oil sector were implemented from 2004 through 2008. However, before these issues are examined further in this brief study it is essential to establish the actual factors behind Russia’s rise to its status as a leading oil exporter in the second quarter of 2009.